Pengembangan Modul Digital Dengan Mengaplikasikan Prinsip Redundansi Pada Mata Kuliah Pengembangan Bahan Belajar - Nuraini, Binti Lutfiyah; Preherdhiono, Henry; Adi, Eka Pramono (Universitas Negeri Malang, 2022)
The development of a digital module for learning materials aims to produce a suitable learning media product in the form of a digital module by applying the principle of redundancy that can accommodate audio, visual, and audio-visual learning styles. In this study, the method used is the research and development approach of Research and Development (R&D) developed by Lee and Owens. The subjects of the digital module trial of learning materials were students majoring in Educational Technology, State University of Malang, who had taken the Learning Material Development course. The product of the digital module for learning materials was tested for its feasibility by material experts and media experts, and 30 students for field trials.Based on the results of the material expert questionnaire, a total percentage of 95% positive responses were obtained, the results of the media expert questionnaire obtained a total percentage of 97% positive responses, and the test results of respondents obtained a total percentage of 89% positive responses.Based on the results of choosing the learning material format between audio, video, and text, it was found that 93.3% of students chose video format material, 23.3% choose audio and 33.3% chose text.So it can be concluded that the digital module media by applying the redundancy principle is suitable for use in the learning process and can also accommodate audio, visual and audio-visual learning styles.AbstrakPengembangan modul digital bahan belajar memiliki tujuan untuk menghasilkan sebuah produk media pembelajaran yang layak berupa modul digital dengan mengaplikasikan prinsip redundansi yang dapat mengakomodasi gaya gaya belajar audio, visual, dan audio-visual. Pada penelitian ini metode yang digunakan adalah pendekatan penelitian dan pengambangan Research and Development (R&D) yang dikembangkan oleh Lee dan Owens. Subjek dari uji coba modul digital bahan belajar adalah mahasiswa S1 Universitas Negeri Malang yang telah menempuh mata kuliah Pengembangan Bahan Belajar. Produk modul digital bahan belajar diuji kelayakannya oleh ahli materi dan ahli media, dan 30 mahasiswa untuk uji coba lapangan. Berdasarkan hasil angket ahli materi diperoleh total persentase 95% tanggapan positif, hasil angket ahli media diperoleh total persentase 97% tanggapan positif, dan hasil uji coba responden diperoleh total persentase 89% tanggapan positif. Berdasarkan hasil pemilihan format materi pembelajaran antara audio, video dan teks diperoleh 93,3% mahasiswa memilih materi berformat video, 23,3% memilih audio dan 33,3% memilih teks. Sehingga dapat disimpulkan media modul digital dengan mengaplikasikan prinsip redundansi layak digunakan dalam proses pembelajaran dan juga dapat mengakomodasi gaya belajar audio, visual dan audio visual mahasiswa.